2018
DOI: 10.1016/j.virol.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

The OC43 human coronavirus envelope protein is critical for infectious virus production and propagation in neuronal cells and is a determinant of neurovirulence and CNS pathology

Abstract: The OC43 strain of human coronavirus (HCoV-OC43) is an ubiquitous respiratory tract pathogen possessing neurotropic capacities. Coronavirus structural envelope (E) protein possesses specific motifs involved in protein-protein interaction or in homo-oligomeric ion channel formation, which are known to play various roles including in virion morphology/assembly and in cell response to infection and/or virulence. Making use of recombinant viruses either devoid of the E protein or harboring mutations either in puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…Virus-cell interactions are always important in the regulation of cell response to infection. For HCoV-OC43, we clearly showed that the viral S and E proteins are important factors of neurovirulence, neuropropagation and neurodegeneration of infected cells [267][268][269]296,312]. We have also demonstrated that the HE protein is important for the production of infectious HCoV-OC43 and for efficient spreading between neuronal cells, suggesting an attenuation of the eventual spread into the CNS of viruses made deficient in fully active HE protein, potentially associated with a reduced neurovirulence [269,295].…”
Section: Mechanisms Of Hcov-induced Neurodegeneration: Possible Assocmentioning
confidence: 78%
See 1 more Smart Citation
“…Virus-cell interactions are always important in the regulation of cell response to infection. For HCoV-OC43, we clearly showed that the viral S and E proteins are important factors of neurovirulence, neuropropagation and neurodegeneration of infected cells [267][268][269]296,312]. We have also demonstrated that the HE protein is important for the production of infectious HCoV-OC43 and for efficient spreading between neuronal cells, suggesting an attenuation of the eventual spread into the CNS of viruses made deficient in fully active HE protein, potentially associated with a reduced neurovirulence [269,295].…”
Section: Mechanisms Of Hcov-induced Neurodegeneration: Possible Assocmentioning
confidence: 78%
“…HCoV-OC43 structural and accessory proteins are important for infection and some clearly represent virulence factors [38,[266][267][268][269]289,295,296]. Using neuronal cell cultures and our murine model, we gathered data indicating that some of these proteins also play a significant role in viral dissemination [269,296] and now aim to exploit these promising leads to fully understand the course and determinants of propagation to and through the CNS and complete the neurologic portrait of short term HCoV neuropathogenesis.…”
Section: Human Coronaviruses In the Cns: Possible Associated Neurologmentioning
confidence: 99%
“…The production of pro-inflammatory cytokines increased and induced neural injuries when human astrocyte culture was infected by HCoV-OC43 (Edwards et al 2000). HCoV-OC43 (Jacomy et al 2006;Stodola et al 2018) caused neuropathy and gliopathy by activating the apoptosis cascades in cell cultures (Jacomy et al 2006). Furthermore, neuroinflammation following by neuroinvasion has been shown in mice when HCoV-OC43 was inoculated intraperitoneally (Jacomy and Talbot 2003).…”
Section: Human Coronavirus Family Has Neuroinvasion Potentialmentioning
confidence: 99%
“…The coronavirus nucleocapsid phosphoprotein is a multifunctional structural protein; during virion assembly it interacts with the viral membrane and forms complexes with genomic RNA. The coronavirus nucleocapsid phosphoprotein plays an important role in coronavirus transcription and assembly as well as the coronavirus lifecycle [28][29][30][31][32][33][34]. The most potent identified compound, 1-[(2,4-dichlorophenyl)methyl]pyrazole-3,5-dicarboxylic acid], may inhibit any of its multifarious activities and functions during virion assembly; however, detailed studies are needed on the inhibitory effect of these compounds on the interaction of nucleocapsid phosphoprotein with the viral membrane, and formation of complexes with genomic RNA during SARS-CoV-2 transcription and virion assembly.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus envelope protein plays a crucial role for the lifecycle of the virus. The small integral membrane protein, the coronavirus envelope protein, is important for the development of the disease in the host through viral assembly, to exit the host cell by viral budding, viral propagation, envelope formation by taking portions of the host cell membranes, and the release of infectious virus from the host cell [33][34][35]. Hence, the SARS-CoV-2 envelope protein was considered for the docking study to identify the most potent compound; the study revealed that mycophenolic acid may an appropriate druggable protein ligand of SARS-CoV-2 to inhibit the development of a COVID-19 by blocking the viral assembly.…”
Section: Discussionmentioning
confidence: 99%